Risk Management Solutions for Supply Shortages - Zami, Dominique (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Mr. Dominique Zami, Manager, PTL Agro - Guadelopue, Ms. Yannick Bock, Manager of the Agriculture and Agro-Food Project, Communauté D'Agglomération Du Nord Grande-Terre - Guadeloupe, Ms. Céline Carles, Environment and Agriculture Officer, DENEL - Martinique